Global, regional, and national burden of chronic kidney disease, 1990-2021: a systematic analysis for the global burden of disease study 2021 - Kaifeng Xie; Haihong Cao; Shiyun Ling; Jiameng Zhong; Haitao Chen; Penghui Chen; Renfa Huang (Frontiers in Endocrinology)
BackgroundChronic kidney disease (CKD) continues to represent a significant public health concern, with both prevalence and incidence rates on the rise globally. Therefore, the study employed the Global Burden of Disease (GBD) database to investigate the global burden of CKD from 1990 to 2021.MethodsThis study utilized data from the GBD 2021. Join-point regression models were developed for the estimation of the average annual percentage change (AAPC) in the prevalence and mortality rates of CKD. Subsequently, stepwise multiple linear regression analysis was conducted to examine the trends in disability adjusted life years (DALYs) and DALYs rate for CKD across diverse populations between 1990 and 2021. Moreover, the influence of age, gender, and socio-demographic index (SDI) on the burden of CKD among patients from 1990 to 2021 was examined. Furthermore, the projection of the burden of CKD from 2022 to 2032 was also conducted.ResultsThe AAPC for prevalence and mortality rates across the entire period spanning 1990 to 2021 was 0.92 and 2.66, respectively. A notable increase in the DALYs and DALYs rate for CKD was demonstrated over time, indicating a growing CKD burden on society since 1990. Furthermore, the DALYs rates for CKD were lowest in the 5-9 year age group for both genders, rising thereafter with age. Notably, the DALYs rate for CKD was higher in males than in females. Regions with higher SDI, generally exhibited a lower burden of CKD, while less developed regions, demonstrated the opposite pattern. Additionally, the age-standardized prevalence and mortality rates for CKD would be projected to increase to 8,773.85 and 21.26 per 100,000 individuals, respectively, by 2032.ConclusionThe research indicated a gradual increase in the global prevalence and mortality rates of CKD over time, which might prompt the formulation of more efficient health policies to alleviate its burden.